Enabling organizational change – leadership, commitment to change and the mediating role of change readiness - Santhidran, Sinnappan; Chandran, V. G. R.; Borromeo, Junbo (Journal of Business Economics and Management, 2013)
There has been little empirical analysis on the complex relationship between leadership, change readiness and commitment to change in the context of Asian countries. In this paper, we propose a research model to analyze the interrelationship between leadership, change readiness and commitment to change using the partial least square technique. Results of the study suggest that leadership positively and significantly affect change readiness but not commitment to change. Consequently, change readiness is found to significantly affect commitment to change. In other words, change readiness is found to mediate the relationship between transformational leadership and commitment to change. This may suggest that the influence of leadership is a sequential process affecting change readiness, and in turn, the commitment to change as opposed to the conventional belief that it affects both change readiness and commitment to change simultaneously. The implication of the study is further discussed.